Combined Heart-Liver and Domino Liver Transplantation in Familial Amyloidosis. Issue 9 (September 2022) - Sickels, Angela; Shah, Keyur B.; Ruch, Brianna; Cotterell, Adrian; Tchoukina, Inna; Quader, Mohammed; Bhati, Chandra; Kumaran, Vinay; Bruno, David; Stravitz, Richard; Levy, Marlon; Kasirajan, Vigneshwar; et al.
Background: Combined heart-liver transplantation (CHLT) is the only curative option for patients with concomitant pathology affecting the heart and liver. In some cases, the native livers of familial amyloidosis (FA) patients may be suitable for domino transplantation into other recipients. Methods: Retrospective analysis (2013 to 2019) of all CHLT at our center was performed. Continuous data were presented as mean with standard deviation and discrete variables as percentages. Results: Familial amyloidosis was the indication for CHLT in 5 out of 6 patients. The mean recipient age was 55 ± 5.62 years. Two patients were bridged with total artificial heart. The mean model for end-stage liver disease score at transplant was 17.17 ± 3.7. Two explanted livers were used for transplantation in a domino fashion. The median intensive care and hospital stays were 5.5 and 19 days, respectively. Complications included renal failure (1), groin abscess (1), pulmonary embolism (1), and cardiac rejection (1). Patient and graft survival for both organs was 100% at a median follow-up of 59 (range 20-76) months. Discussion: Combined heart-liver transplantation for FA achieves excellent outcomes. The possible use of livers explanted from patients with FA for domino liver transplantation can contribute to the liver donor pool.